Kurdish Maternity Nurses' Perspectives About Human Dignity - Tiran Jamil Piro (Iran University of Medical Sciences, 2016)
Background: Ethical standards of nursing profession emphasize that taking care of patients, showing respectful behavior, and preserving patients' human dignity are important nursing priorities. Furthermore, since time immemorial, humanistic thinkers have always paid close attention to the issues of humanity and human dignity. Despite the emphasis of nursing texts on the importance of preserving the patients' human dignity, this concept has seldom been considered by nursing scholars, and very few clinical studies have focused on it. To explore the nurses' perspectives about human dignity in Hawler Maternity Hospital, Kurdistan, Iran. Methods: A qualitative content analysis design was used to analyze the study data. After using a purposive sampling method, 10 Kurdish nurses who worked in Hawler Maternity Hospital were recruited for the study. Then, semi-structured interviews were carried out to collect data. Data analysis was done through conventional content analysis. This research was approved by the Ethics Committee of College of Nursing, Hawler Medical University. Results: Through the data analysis, three main themes emerged: 1) mothers' deprivation of basic health care services, 2) women's right to have sympathetic care, and 3) negligence of the mothers' human rights from different aspects. Conclusion: Based on participants' opinions, respecting mothers' human dignity means establishing a sympathetic relationship with them. Furthermore, institutionalization of human dignity and value in humans' nature is one of the crucial care factors.